2013
DOI: 10.1186/1476-511x-12-130
|View full text |Cite
|
Sign up to set email alerts
|

Associations of genetic polymorphisms of SAA1 with cerebral infarction

Abstract: BackgroundSerum amyloid A protein (SAA) is both an inflammatory factor and an apolipoprotein. However, the relation between genetic polymorphisms of SAA and cerebral infarction (CI) remains unclear.Methods and resultsThe previously reported 4 Single Nucleotide Polymorphisms (rs12218, rs4638289, rs7131332, and rs11603089) of SAA1 gene were genotyped by TaqMan method in a case–control study including 287 cerebral infarction patients and 376 control subjects. We found rs12218 CC genotype and rs7131332 AA genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Recently, Xie et al reported that rs12218 polymorphism in SAA1 gene was associated with IMT [ 17 ], HDL-C [ 18 , 19 ], Ankle-brachial index (ABI) [ 20 ], and plasma uric acid levels [ 18 ] which was related to cardiovascular disease in adults. And Zhang et al reported SAA1 gene polymorphism was associated with cerebral infarction [ 21 ]. Xu et al also reported SAA1 gene polymorphism was associated with lipid levels [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Xie et al reported that rs12218 polymorphism in SAA1 gene was associated with IMT [ 17 ], HDL-C [ 18 , 19 ], Ankle-brachial index (ABI) [ 20 ], and plasma uric acid levels [ 18 ] which was related to cardiovascular disease in adults. And Zhang et al reported SAA1 gene polymorphism was associated with cerebral infarction [ 21 ]. Xu et al also reported SAA1 gene polymorphism was associated with lipid levels [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CC genotype of rs12218 was more frequent among patients suffering from coronary artery disease (Xie et al, 2015). This genotype was also more frequent in patients suffering from cerebral infarction (Zhang et al, 2013a). In comparison, the TT genotype of rs12218 is associated with an increased serum uric acid level (Xie et al, 2012) and with susceptibility to osteoporosis (Feng et al, 2013).…”
Section: Human Saa1 Polymorphism and Disease Dispositionmentioning
confidence: 97%
“…Numerous studies have shown that various environmental variables and genetic variations contribute to the etiology of CI. 12 Previously published studies showed that ApoE polymorphisms have been associated with CI, although with varying degrees of success. 13 , 14 In the present case, the ε3/ε3 genotype and ε3 allele were significantly lower in patients than the controls, indicating its potential protective role.…”
Section: Discussionmentioning
confidence: 99%